Importance of TP53 codon 72 and intron 3 duplication 16bp polymorphisms in prediction of susceptibility on breast cancer - Costa, Sandra (2008)
Background: TP53 is one of major tumour suppressor genes being essential in preservation of genome integrity. Two very common polymorphisms have been demonstrated to contribute to cancer susceptibility and tumour behaviour. The purpose of this study was to evaluate the role of Arg72Pro and PIN3 Ins16bp polymorphisms in TP53 gene as genetic susceptibility and predictive markers to breast cancer.Methods: We analysed DNA samples from 264 breast cancer patients and 440 controls, for TP53 Arg72Pro and PIN3 Ins16bp polymorphisms using PCR-RFLP.Results: We observed that women with A2A2 genotype have increased risk for developing breast cancer, either in women with or without familial history (FH) of the disease (OR = 4.40, 95% CI 1.60 - 12.0; p=0.004; OR=3.88, 95% CI 1.18 - 12.8; p=0.026, respectively). In haplotype analysis, statistically significant differences were found between TP53 Arg-A2 haplotype frequencies and familial breast cancer cases and the respective control group ( OR=2.10, 95% CI 1.08 - 4.06; p=0.028). Furthermore, both TP53 polymorphisms are associated with higher incidence of lymph node metastases.Conclusion: Our findings suggest TP53 PIN3 Ins16bp polymorphism as a real risk modifier in breast cancer disease, either in sporadic and familial breast cancer. Furthermore, both TP53 polymorphisms are associated with higher incidence of lymph node metastases.